Technique et science informatiques - Outin Helene (Paris : Hermes, 1995)
Constraint logic proramming has proved to be a successful field of research fom both the theoretical and practical points of view. it combines the ease of programming and the declarativity of logic programming with the power and efficiency of computing on particular domains, thanks to specific and optimized tools (constraints solves).We propose a survey of this domain presenting the main research topics.
Keywords: Science informatiques; Technique